A jigsaw guide to making sense of the world - McLellan, Alex, 1968- (Downers Grove, IL : IVP Books, 2012)
McLellan explores competing views of truth and belief and examines the nature of doubt. Ultimately Christianity is reasonable because it resonates with how we see and experience the world. Even if we don't have absolute certainty, we have enough to go on to have confidence in the Christian worldview. --from publisher description
Seeing the big picture -- Jigsaw: be prepared to see it -- Truth: be prepared to handle it -- Belief: be prepared to share it -- Faith: be prepared to anchor it -- Doubt: be prepared to deal with it -- Big picture: be prepared to show it.
Includes bibliographical references.
Description based on print version record.
Keywords: Christianity -- Philosophy; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books